2023
DOI: 10.1039/d3fo02986g
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation with astaxanthin enhances anti-tumor immune response and aids the enhancement of molecularly targeted therapy for hepatocellular carcinoma

Pengfei Ren,
Xinyue Yu,
Han Yue
et al.

Abstract: Astaxanthin promoted the infiltration of CD8+ T cells into the tumor microenvironment and elevated the levels of Granzyme B. In addition, astaxanthin regulated the intestinal flora composition of tumor-bearing mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
(75 reference statements)
0
5
0
Order By: Relevance
“…The differential microorganisms in the intestinal flora of mice following fecal transplants were similar to those observed in our previous experiments. 10,17 These results suggest that these bacteria may be key genera for astaxanthin-targeted regulation. Additionally, we established a correlation between these distinct microorganisms and significantly varied metabolites in the serum of mice with tumors following cecal transplants.…”
Section: Disscusionmentioning
confidence: 88%
See 3 more Smart Citations
“…The differential microorganisms in the intestinal flora of mice following fecal transplants were similar to those observed in our previous experiments. 10,17 These results suggest that these bacteria may be key genera for astaxanthin-targeted regulation. Additionally, we established a correlation between these distinct microorganisms and significantly varied metabolites in the serum of mice with tumors following cecal transplants.…”
Section: Disscusionmentioning
confidence: 88%
“…11 Furthermore, astaxanthin had a notable impact on the composition of the intestinal flora in H22 mice. 10 Recent studies have shown that intestinal flora are essential for maintaining the body's physiological homeostasis. 22 Hence, we propose that astaxanthin primarily acts on the intestinal flora to alleviate skeletal muscle atrophy in cancer-associated cachexia.…”
Section: Disscusionmentioning
confidence: 99%
See 2 more Smart Citations
“…LefSE analysis identified that Akkermansia was the only bacteria with a relative abundance change exceeding 1% in the AX group compared to the HFD group. Numerous studies had reported a growth of Akkermansia following AX supplementation [ 37 , 38 , 62 ]. A decreased abundance of Akkermansia was associated with various diseases such as obesity, diabetes and liver steatosis, while Akkermansia supplementation exhibited anti-obesity effects and improve metabolic disorders induced by HFD [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%